Security Regional Division of Farmland Soil Heavy Metal Elements in North of the North China Plain - Kong, Chenchen; Zhang, Shiwen (Frontiers in Environmental Science, 2021)
A total of 94 soil samples in different soil depth (0~25cm, 25~50cm) were collected of farmland soil around the plain of Beijing, and the concentrations of five heavy metal elements (Cd、Cr、Pb、As、Hg) were measured by using standard methods. The safety utilization evaluation method of heavy metal was built based on geo-accumulation index, improved geo-accumulation comprehensive index and potential ecological risk index. Then, the governance principles and specific management control strategy were determined detailedly according to the core pollution source analysis of each safety grade zone. The results showed that there were four different comprehensive safety utilization zones: safe utilization, low-risk, middle-risk and high-risk. The risk level basically showed a trend of weakening from the center of the city to the periphery, among which the low-risk states were dominated. Based on the characteristics of different security zones, this study put on the governance principles of priority protection, long-term monitoring and moderate optimization, strengthen early warning and cooperate with effective repair, priority governance. And then put forward practical control strategies according to the core pollution sources of each safety utilization zone. Our findings may provide a clear direction for rational utilization of land resources and renovation in the future.